Managers, can you hear me now? : hard-hitting lessons on how to get real results - Strigl, Denny F.; Swiatek, Frank (McGraw Hill-Ascent Audio, 2011)
The former head of Verizon is talking. Can you afford not to hear what he has to say? Are you delivering? For managers, behavior is the real key to achievement. In order to stop struggling and start delivering, you need to close the gap between what you know and what you do. That's been Denny Strigl's method, and now it can be yours, too. Among the most prominent architects of the wireless communications industry, the former Verizon Wireless president and CEO has had one of the most remarkable careers in modern business. In Managers, Can You Hear Me Now?, Strigl shares all the skills and techniques he used to build Verizon into one of the greatest growth companies in any industry. You'll learn how to: Create a corporate culture where trust, respect, and integrity flourish- and employees and customers alike are appropriately served "Eliminate the fluff," get focused, and stop wasting time on things that don't matter Address issues proactively before they become problems--even employee performance issues Get past your "blind spots," reinforce priorities consistently, and communicate with clarity Master the Four Fundamentals of Management: growing revenue, getting new customers, keeping the customers you already have, and eliminating costs Managers, Can You Hear Me Now? includes additional suggestions for bringing the best of your energy and passion into your work, helpful anedcotes from Strigl's career, simple self-assessment questions, and even a look at how your business day as a successful manager should play out. Whether you're the CEO of a large corporation or run your own small business, the lessons from Managers, Can You Hear Me Now? are sure to come through--loud and clear.